Health Literacy and Utilization of Reproductive Health Services Among High School Students - Izzatul Arifah; Afrin Linda Dewi Safari; Diella Fieryanjodi (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2022)
Background: Utilization of reproductive health service may improve adolescent health and prevent reproductive health problems in adulthood. However, the proportion of adolescents who uses the available services remains low. Many factors influenced the services use among adolescents. The relation of adolescents’ health literacy and reproductive health service use was not fully understood. This study intended to examine the relationship between health literacy and use of reproductive health counseling service among high school students in one school in Banyumas Regency, controlling other variables (knowledge, acceptability, age, and sex). Method: A cross-sectional study was conducted in March-April 2021 in one high school (SMA Negeri 4 Purwokerto), Banyumas regency, Central Java Province. Samples were 170 students purposively chosen from the first and second grade who were willing to fill the self-administered online questionnaire. Data of health literacy were collected using eHEALS questionnaire. Other data were obtained using valid and reliable self-design questionnaires. Multiple logistic regression was deployed to analyze the relationship between variables. Results: Health literacy had a significant relationship with the use of reproductive health services among adolescents. The probability of the reproductive health counseling service was doubled if they had a good health literacy level among students who had high acceptability toward the service and were female with an OR value of 2.1 (95% CI 1.01-4.49). In conclusion, adolescent’s health literacy level is associated with the utilization of reproductive health services. Further research is needed to confirm the association between the variables in more extensive settings.